Examining the evolving roles of quantity surveyors in achieving the United Nations sustainable development goals - Juanita Seyram Gasu; Kenneth Eluerkeh; Kezia Nana Yaa Serwaa Sackey; Gabriel Nani; Annabel Morkporkpor Ami Dompey; Eric Simpeh; Kofi Agyekum (PLoS ONE, 2026)
The roles of Quantity Surveyors (QSs) in the construction industry are vital, yet their contribution to sustainability has been underexplored. This study examines the roles of quantity surveyors in achieving the 17 Sustainable Development Goals (SDGs) towards advancing the 2030 global agenda. A structured questionnaire was used to solicit the views of 88 professional QSs working with various firms registered with the Ghana Institute of Surveyors (GhIS) on the theme under investigation. The data gathered were analyzed using descriptive (frequencies, percentages, mean) and inferential (Fuzzy Synthetic Analysis) statistics. The Fuzzy Synthetic Analysis revealed that QSs play critical roles in Social Development and Education (index 4.300), Environmental Sustainability and Resource Management (index 3.933), Poverty Alleviation and Food Security (index 3.696), and Economic Growth and Infrastructure Development (index 3.619). The findings not only highlight the critical impact of QSs in various SDG-related areas but also reveal substantial gaps that need to be addressed to meet the 2030 targets. Although there is a growing interest in research on the UNSDGs in the construction industry, professional Quantity Surveyors have yet to prioritize the SDGs when carrying out their roles. Using Fuzzy Synthetic Analysis, this study reveals important insights into QSs’ roles in achieving the SDGs. The four identified critical roles serve as a model for QSs and other professionals to use as indices in future projects to help achieve the SDGs by 2030.